Successful single-dose teicoplanin prophylaxis against experimental streptococcal, enterococcal, and staphylococcal aortic valve endocarditis. - Perdikaris, G S (1997)
Teicoplanin is a glycopeptide antibiotic that is administered both intramuscularly and intravenously. It has a prolonged half-life and a less toxic profile in comparison to those of vancomycin. The efficacy of a single dose of teicoplanin (18 mg/kg of body weight given intramuscularly) for the prevention of endocarditis due to Streptococcus oralis, Enterococcus faecium, and methicillin-resistant Staphylococcus aureus (MRSA) was evaluated after applying the rabbit model. Vancomycin at a single dose of 30 mg/kg given intravenously was used as the comparative agent for the prevention of endocarditis due to MRSA and E. faecium, while ampicillin at a single dose of 40 mg/kg given intravenously was used as the comparative agent for the prevention of endocarditis due to S. oralis. Rabbits in the teicoplanin group were infected at 1 h postdosing with approximately 10(7) CFU of each strain. Rabbits in the other groups were infected at 0.5 h postdosing with approximately 10(7) CFU of S. oralis (ampicillin group) or E. faecium and MRSA (vancomycin group). All rabbits were sacrificed 5 days later. Teicoplanin and vancomycin protected the animals challenged with E. faecium by 87.5 and 50%, respectively, and protected the animals challenged with MRSA by 100 and 92%, respectively. Teicoplanin and ampicillin protected the animals challenged with S. oralis by 100 and 77%, respectively. Prevention of endocarditis by teicoplanin was likely to be due to a prolonged inhibition of bacterial growth by the sustained supra-MICs. It is concluded that teicoplanin is very effective in preventing experimental streptococcal, enterococcal, and staphylococcal endocarditis and may be an attractive alternative antibiotic in patients allergic to beta-lactams, especially in the outpatient setting.